2021
DOI: 10.3389/fpsyt.2021.764054
|View full text |Cite
|
Sign up to set email alerts
|

Use of Technology and Its Association With Academic Performance and Life Satisfaction Among Children and Adolescents

Abstract: Introduction: In the last years, there has been a rise in the use of technology among children and adolescents, which has led to a greater concern about its impact on their socioemotional and cognitive development.Aims: To explore the time spent using technology, the risk perception of its use by students, and the association between frequency of technology use and life satisfaction and academic performance among children and adolescents in Chile. Additionally, we explored the mediating effect of sleep depriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Finally, the present study did not examine the role of the context of technology use on the associations of problematic technology use with academic performance and school connectedness, because the question on context of technology use was not asked to students. This is particularly important because previous studies have showed that the association between technology use and academic performance may differ between weekdays and weekends [ 60 , 61 , 62 ]. Future research that simultaneously measures problematic technology use and the specific context of technology use is needed to better understand its impact on the associations of problematic technology use with academic performance and school connectedness among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present study did not examine the role of the context of technology use on the associations of problematic technology use with academic performance and school connectedness, because the question on context of technology use was not asked to students. This is particularly important because previous studies have showed that the association between technology use and academic performance may differ between weekdays and weekends [ 60 , 61 , 62 ]. Future research that simultaneously measures problematic technology use and the specific context of technology use is needed to better understand its impact on the associations of problematic technology use with academic performance and school connectedness among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time spent on mobiles and playing video games correlated with lower self-reported academic performance (32). This relationship was mediated by sleep deprivation, suggesting that the negative impact on academic performance may be in uenced by the lack of su cient sleep rather than the use of mobiles and video games per se (32). Furthermore, social media platforms can have adverse effects on a person's mental and emotional well-being, particularly in increasing levels of anxiety when preferring the immediate grati cation of use rather than working on a long-term goal such as academic goals (35).…”
Section: Mental Health Among Youth From Rural Areasmentioning
confidence: 94%
“…While one study argues that adolescents who spend more than three hours per day engaged in online gaming are more likely to experience a range of mental and psychosomatic health issues (34), another study found that the amount of time spent using technological devices had no signi cant association with life satisfaction (32). However, the time spent on mobiles and playing video games correlated with lower self-reported academic performance (32).…”
Section: Mental Health Among Youth From Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…[47], [24], [25], [26], [48], [49], [27], [28], [50], [51], [26], [52], [53], [54], [55], [29], [30], [56], [3], [57] Multimedia These articles denote that the uses of multimedia applications achieve a better environment for cognitive development and improve academic performance. Where every visual demonstration is important for training.…”
Section: Categories Themes and Functionality Referencesmentioning
confidence: 99%